2003
DOI: 10.1046/j.1528-1157.2003.08003.x
|View full text |Cite
|
Sign up to set email alerts
|

Short Course of Prednisolone in Indian Patients with Solitary Cysticercus Granuloma and New‐onset Seizures

Abstract: Summary:Purpose: To evaluate the role of a short course of oral corticosteroids in Indian patients with solitary cysticercus granuloma with seizures. Methods:In this open-label, randomized, prospective followup study, 97 patients with new-onset seizures and a single enhancing computed tomography (CT)-detected lesion of cysticercosis were randomly divided in two groups to receive either antiepileptic monotherapy alone (n = 48) or antiepileptic monotherapy with prednisolone (n = 49). The patients in the latter g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 22 publications
(22 reference statements)
0
51
1
3
Order By: Relevance
“…The lesion was considered 'partially resolved' if, on visual analysis, there was a substantial reduction in the amount of perilesional oedema and size of the lesion. 3 The statistical analysis was done by using chisquare test for categorical observations. Student's t test to compare continuous observations such as age, onset, number of seizures, and duration of illness between two groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lesion was considered 'partially resolved' if, on visual analysis, there was a substantial reduction in the amount of perilesional oedema and size of the lesion. 3 The statistical analysis was done by using chisquare test for categorical observations. Student's t test to compare continuous observations such as age, onset, number of seizures, and duration of illness between two groups.…”
Section: Methodsmentioning
confidence: 99%
“…Short-term prednisolone therapy helps in rapid resolution of solitary cysticercus granuloma in Indian patients with new-onset seizures. 3 The present study was planned to confirm the role of a short course of oral corticosteroids in patients with solitary cysticercus granuloma by a double-blind placebo-controlled study.…”
Section: Introductionmentioning
confidence: 98%
“…Treatment regimens consisted of prednisolone 1 mg/kg for 10 days with a 4-day taper with and without antiepileptic treatment, prednisolone 1 mg/kg for 7 days with a 3-day taper without antiepileptic treatment and methylprednisolone 1 g/1.72 m 2 for 5 days without antiepileptic treatment. All studies showed a decrease in epileptic seizures and three showed a significant clearance of cysts on CT [122][123][124][125].…”
Section: Antihelminthic And/or Anti-oedematous Treatmentmentioning
confidence: 99%
“…2). [11][12][13][14] Patients with massive infections, conversely, carry poorer prognosis. If a lesion resolves but leaves a calcified scar, the prognosis for seizure relapse is poorer.…”
Section: Types Of Nccmentioning
confidence: 99%